Influence of Some Extraction Conditions Factor on Phenolic Content and Antioxidant Activity of Solanum betaceum Cav. - Erna Prawita Setyowati; Andayana Puspitasari; Dias Insan Afini; Farida Hanum Nasution; Rosyidatun Nafingah (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Solanum betaceum Cav. fruit is renowned for having antioxidant activity because it contains phenolic compounds. This study aimed to determine the effect of some condition factor namely solvent composition, maceration time, liquid-solid ratio, and the particle size of S. betaceum Cav fruit to the total phenolic content and antioxidant activity. The fruit was collected from Temanggung, Wonosobo, and Kopeng, Central Java, Indonesia. The research used single-factor experiments and simplex lattice design (SLD) as an optimization method. Total phenolic content was determined using Folin Ciocalteau reagent, while antioxidant activity was determined using 2,2-diphenyl-1-picrilhidrazil (DPPH) radical scavenger activity. The solvent combination which gave the highest responses was ethanol: water (60:40 v/v) with phenolic content of 7.48% w/w EAG. Maceration for 8 hours will produce an extract with the highest total phenolic content (8.76% w/w EAG). The optimal solvent ratio was at 10:1 v/w with total phenolic content of 7.26 ± 0.20% w/w EAG. The optimum particle size was 600-850 μm with a total phenolic content of 6.07 ± 0.18% w/w EAG. Antioxidant activity with the DPPH free radical scavenger capture method from three regions did not show significant results.